Seventeen Group Music and Indomilk: A Critical Discourse Analysis of Language and Power in Celebrity Endorsement - Fortuna, Nurkhaira Ariendita; Athyah, Andi Ummy; Amin, Fatimah Hidayahni; Sunusi, Seny Luhriyani; Hanafie, Nurharsya Khaer (Journal for Teaching and Education for Scholars, 2025)
This study analyzes language and power relations in celebrity endorsement through the lens of SEVENTEEN’s advertisement for Indomilk. Although celebrity endorsements are known to influence purchasing decisions, there is scant focus on the discourse celebrities strategically employ, especially in the context of K-pop. Fairclough’s three-dimensional Critical Discourse Analysis (CDA) was used in this research to capture how SEVENTEEN’s language choices in their endorsement critically constrain or reproduce the power dynamics relations of the brand, the celebrities, and the consumers. Headed from June 2024 to March 2025, the study collected television and social media ads targeting specific audiences, alongside numerous other pieces of marketed dialogue and visuals. The data were examined at multi-levels: textual, discursive, and social practice. The results indicate that the primary narrative of the ads was to promote Indomilk not simply as a drink but as a vessel of joy, vigor, and global citizenship visually and textually via relatable marketing image and emotionally resonant vernacular. Culturally, the endorsement is framed in Korean with outlandish and groundless suggestions to defy any local inklings of identity which simultaneously aids the brand’s appeal among young local audiences amplifying brand loyalty. The research also notes the portrayals change when it comes to male idols as they perform emotive expressiveness and soft masculinity, which contributes to changing cultural traditions. The results of this study highlight how celebrity discourse operates as a site of socio-cultural and business appropriation, affixing brand power and molding identity of clientele.